ANALISA YURIDIS TERHADAP PENERBITAN SERTIFIKAT HAK GUNA BANGUNAN DI WILAYAH LAUT PANTAI INDAH KAPUK 2 - Octaviani, Defitria; Hendrawarman Hendrawarman (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research conducts a juridical analysis of the issuance of Building Use Rights (HGB) certificates in the sea area of Pantai Indah Kapuk (PIK) 2, a geographically reclaimed area. The study uses a normative juridical method. The research findings conclude that: (a) Building Use Rights (HGB) certificates cannot be issued over the sea or waters because, legally, the sea is not an object that can be encumbered with such rights. The